Arabic translation, cultural adaptation, and validation of the BDDQ-AS for rhinoplasty patients - Ahmed S. Abdelhamid; Saad Elzayat; Mohamed A. Amer; Hossam S. Elsherif; Garyfalia Lekakis; Sam P. Most (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Body Dysmorphic Disorder (BDD) is a significant aspect that compromises patient satisfaction after rhinoplasty. BDDQ-AS (Body Dysmorphic Disorder Questionnaire-Aesthetic Surgery) is a validated, simple, reliable patient-reported outcome measure. It is a screening tool to detect body dysmorphic disorder in rhinoplasty patients. This study aimed to translate, culturally adapt, and validate BDDQ-AS to Arabic as a novel tool for screening and detecting BDD in Arabic rhinoplasty individuals. Methods BDDQ-AS was translated from English to Arabic following the international consensus guidelines. We tested the translation on ten Arabic-speaking rhinoplasty patients to ensure that the final version was understandable and acceptable. The proposed Arabic version was then completed by 112 patients whose average age was 28.79 ± 9.32 years. The screening is assumed positive if the patients expressed bother and preoccupation about their appearance (questions 1 and 2 “yes”), as well as a moderately disrupted everyday life (question 7 "yes" or questions 3, 4, 5, or 6 are equal to or greater than “3′′). The internal consistency, test–retest reliability, and item-response theory (IRT) were used to evaluate psychometric validations. Results The Arabic BDDQ had a high level of internal consistency, as measured by Cronbach's alpha 0.995. The A-BDDQ-AS was deemed reliable with an Intraclass Correlation Coefficient (ICC) of 0.989. A-BDDQ had good discrimination scores (above 2.0) with adequate difficulty parameters. The overall scale content validity average was 0.83, affirming that all items were relevant, clear, and straightforward. Conclusion The Arabic version of the BDDQ-AS is reliable, culturally adapted, and psychometrically validated to be readily used and incorporated into clinical practice. It is a beneficial tool that can guide the screening of Arabic rhinoplasty patients suffering from body dysmorphic disorder and be utilized in further studies to optimize patient outcomes. Graphical Abstract